A solution to the age-stiffening problem in natural rubber and polybutadiene elastomers - Halladay, J.R.; Hedlund, C. (My University, 2014)
Natural rubber (NR) and polybutadiene (BR) elastomers are used in the manufacture of many vibration isolation devices in rotorcraft, including high-capacity laminate (HCL) rotor bearings and Fluidlastic™ blade dampers. Investigations show that all conventionally-formulated NR and BR elastomers stiffen over time during storage at ambient conditions and they also stiffen when aged at elevated temperatures. Studies determined that an increase in the elastic shear modulus G’ of 8% to 12% in six months is not out of the ordinary for a typical NR/BR blend, and the increase in stiffening continues for years with no evidence of reaching an asymptote. A proprietary chemistry that significantly reduces the magnitude of age-stiffening has been discovered. Although the specific chemistry is not disclosed, the data demonstrates that it is possible to greatly reduce both shelf age-stiffening and stiffening due to heat ageing without sacrificing the fatigue resistance associated with conventional sulfur cure systems.